Peningkatan kemampuan motorik halus melalui bermain playdough di taman kanak-kanak qur’aniah air runding pasaman barat - Isnani Sari; Rakimahwati Rakimahwati (IICET (Indonesian Institute for Counseling, Education and Therapy), 2018)
This study aims to improve children's fine motor skills through playing playdough in Qur’aniah Air Runding Pasaman Barat. The type of research is Classroom Action Research conducted in a cyclical way that is two cycles of each cycle three meetings. which was held in Qur’aniah Air Runding Child B group with 15 children consisting of 8 men and 7 women. The research procedure is done as much as II cycle. Data collection techniques used observation and documentation techniques. Based on the results of the research, it can be seen that playdough can improve the fine motor skills of children in Qur’aniah Air Runding Pasaman West, with the percentage of the average value of the category developed very well that has reached the Minimum Criterion (KKM).